Formação de agentes de Cultura Digital Maker: avanço, desafio e possibilidades - Moreira, José César Pontes (2023)
The aim of this work was to discuss and analyze the Training of Agents of Digital Maker Culture as a strategy for the teaching and learning process, placing the subjects in practical, reflective, fast, cooperative, collaborative, innovative and effective learning. The word “active” is used in the adjectives referring to Maker training, as they truly reflect the attitude that the course participants/students should have during the Maker didactic experience. Maker culture is understood as a learning and teaching movement in which everyone learns by putting their “hands in the dough”, effectively studying and putting it into practice, applying it at the same time as learning. The process is dynamic, intelligent in the sense of seeking solutions and establishing relationships of collaboration, creation and co-creation, all resulting in products or possible solutions to individual or societal problems. It's the “Do It Yourself” (FVM) philosophy or as it's known worldwide as “Do It You Self” (DIYS) and “Let's Do It Together” or “Do It With Others”. To do this, we first carried out a bibliographic survey of specialized literature, national and international texts on digital maker culture and the digital skills needed for development in public and private institutional teaching spaces. The first result of this study was the preparation of 8 (eight) articles, 8 of which have already been published in journals and books, and 1 of which is about to be submitted and published. These articles, as well as being products of this thesis, also served as a theoretical framework for analyzing the phenomena observed during the extension course called “Training Agents of Digital Maker Culture” with a workload of 50 hours, held in the first semester of 2023, with the support of the Labpam Laboratory (FACED/UFC). Through the actions during the course, it was possible to observe and analyze the behavior of the teachers/course participants, as well as the didactic strategies and the satisfaction process of the course participants who learned new concepts and practices quickly, with short-term results, giving them a feeling of potential during the practical activities and confidence in learning at each meeting of the course. The course was divided into 6 (six) modules, namely: 01. Arduino training; 02. Educational software; 03. Maker culture; 04. Preventive maintenance; 05. 3D modeling; and, 06. Portfolio which were sufficient to validate the efficiency and effectiveness of maker didactics as an interactive, engaging and innovative teaching resource. In each class, the process of discovery and innovation was revealed in the commitment, enthusiasm, curiosity and creativity of each subject. As a result, the course participants presented 8 works at the end of the course, generated from what they had learned and with the effective use of the 3D printer, 3D pen and electronic boards and other components. It was concluded that the training of digital maker culture agents contributes to the training of teachers and students. Another point that was clearly presented was that the training process has subjective and objective results, which are seen in the materiality, but the subjective ones are revealed in the self-discovery and self-composition of the course participants as subjects capable of learning new concepts and applications in a playful, collaborative way and with results that are present in the simplicity of the “magic” of making or “getting your hands dirty” without fear and with the right environment for these fantastic experiments, which is to create, co-create, learn, relearn, try, make mistakes, produce, test and generate products. Finally, it also emerged that among public school teachers there is a demand for this type of practical, direct training in accessible language. The digital maker culture has proved to be another teaching resource, but because of its interdisciplinary nature and application, it goes beyond the classroom and laboratories and can contribute to solving problems at home, in companies and in the entrepreneurship movement, which is growing stronger as an economic strategy for social sustainability, and can revolutionize the way we produce and live in society. Based on these conclusions, various educational studies can be carried out on maker culture and the maker movement as a process that is quietly revolutionizing the world's economy and culture.